Bioactive polysaccharides from lotus as potent food supplements: a review of their preparation, structures, biological features and application prospects - Dai, Guona; Wang, Jiale; Zheng, Jiamei; Xia, Conglong; Wang, Yaping; Duan, Baozhong (Frontiers in Nutrition, 2023)
Lotus is a famous plant of the food and medicine continuum for millennia, which possesses unique nutritional and medicinal values. Polysaccharides are the main bioactive component of lotus and have been widely used as health nutritional supplements and therapeutic agents. However, the industrial production and application of lotus polysaccharides (LPs) are hindered by the lack of a deeper understanding of the structure–activity relationship (SAR), structural modification, applications, and safety of LPs. This review comprehensively comments on the extraction and purification methods and structural characteristics of LPs. The SARs, bioactivities, and mechanisms involved are further evaluated. The potential application and safety issues of LPs are discussed. This review provides valuable updated information and inspires deeper insights for the large scale development and application of LPs.